The Affordable Care Act : advancing long-term care policy in the United States - Miller, Edward Alan (New York, New York : Routledge, 2013)
Overview: Long-term care in the United States and other countries suffers multiple problems. Many people find it difficult to afford the high costs of services available and there is often inadequate care coordination, which compromises care quality, particularly amongst those eligible for multiple public programs. Recruitment and retention of a well-trained, stable workforce is also considered a challenge that needs to be addressed. The policy debate leading up to the Patient Protection and Affordable Care Act (ACA) drew attention to prevailing deficiencies in the way long-term care is delivered, regulated, and financed in the United States. This collection reviews what was accomplished by the legislation and what still remains to be done. Just how effective is the ACA likely to be in addressing the challenges plaguing the long-term care sector? Did it result in meaningful change or make little impact? This book answers these questions, drawing contributions from among the most eminent long-term care experts in the United States. This book was originally published as a special issue of the Journal of Aging & Social Policy.
Citation information -- Notes on contributors -- Introduction: the Affordable Care Act and long-term care: comprehensive reform or just tinkering around the edges? / Edward Alan Miller -- CLASS Act: is it dead or just sleeping? / Joshua M Wiener -- 10-foot rope for a 50-yard drop: the CLASS Act in the patient protection and Affordable Care Act / William G Weissert -- Partnership long-term care insurance: lessons for CLASS Act program development / Mark R Meiners -- Medicaid home- and community-based services: impact of the Affordable Care Act / Charlene Harrington, Terence Ng, Mitchell LaPlante and H Stephen Kaye -- Impact of health care reform on the workforce caring for older adults / Robyn I Stone and Natasha Bryant -- Nursing homes and the Affordable Care Act: a cease fire in the ongoing struggle over quality reform / Catherine Hawes, Darcy M Moudouni, Rachel B Edwards and Charles D Phillips -- Care coordination for dually eligible medicare-medicaid beneficiaries under the Affordable Care Act / David C Grabowski -- Medicare and the Affordable Care Act / Marilyn Moon -- Conclusion: Affordable Care Act, long-term care, and elders: two steps forward, one step back / Pamela Nadash and Edward Alan Miller -- Index.
'This book is a reproduction of the Journal of aging & social policy, volume 24, issue 2'--T.p. verso.
Includes bibliographical references and index.
Keywords: United States; Long-term care of the sick -- Government policy -- United States; Older people -- Long-term care -- Government policy -- United States; Older people -- United States -- Social conditions; Health care reform -- United States